Malignancies associated with GIST: a retrospective study with molecular analysis of KIT and PDGFRA - Mayr, Patrick; Märkl, Bruno; Agaimy, Abbas; Kriening, Bernadette; Dintner, Sebastian; Schenkirsch, Gerhard; Schneider-Stock, Regine (Langenbecks Archives of Surgery, 2019)
Purpose: Gastrointestinal stromal tumors (GISTs) are the most common soft tissue tumors of the GI tract. Studies have been published reporting additional neoplasms in GIST patients. This study aimed to evaluate possible associations of mutation type, morphology, and clinical aspects of GISTs. Methods: All cases of GIST were identified from our pathology files. Coding exons of KIT and PDGFRA in GISTs with additional malignancies were sequenced. Results: A total of 70 of 188 (37%) retrieved patients with confirmed diagnosis of GIST showed at least one additional malignant neoplasm. Fifty of these GISTs were located in the stomach (71%), 8 in the small intestine (11%), 5 in the colon/rectum (7%), and 7 cases (6.2%) were of undetermined sites of origin. The distribution of identified mutations was similar to that described in GISTs without secondary malignancies. A total of 37 of 57 cases (65%) showed mutations in the KIT gene exon 11, 3 (5%) cases in exon 9, and 1 (2%) case in exon 13. Nine tumors (16%) had mutations of the PDGFRA gene. KIT and PDGFRA wild-type status were found in seven cases (12%). Most of the secondary neoplasms were located within the GI tract (34%), in the urogenital system (24%), or the breast/female genital tract (20%). Conclusion: This study confirms the high rate of additional malignant tumors in GIST patients. GIST features in these cases are very similar to those with sole GIST.
CRIS-Team Scopus Importer:2019-08-13
Keywords: Additional/secondary malignancy; Gastrointestinal stromal tumor; GIST; KIT; Mutation; PDGFRA